Exceptional leadership by design how design in great organizations produces great leadership - Breen, Jennifer Moss; Elkington, Rob; Glick-Smith, Judith; Van der Steege, Madeleine (Emerald Publishing Limited, 2018)
Imagine a world with great leadership. What would that world be like? Would it be a better world or a worse one? Now ratchet great leadership up to exceptional leadership and suddenly we have cause for optimism. But how do we design exceptional leadership, and would we even know it if we saw it? Traditional paradigms of leadership have celebrated decisive top-down control and analytical decision-making. But times are changing. The world is more connected, complex, fluid and interdependent.This book debunks the myth that leaders need to be creative like designers to apply Design Thinking. Applying design approaches and practices to organizational leadership is not just about its leaders becoming more creative. It is definitely not about the person at the top coming up with the grand answer. Design thinking starts with the pain point related to the problem you are trying to solve. You get to the heart of the issue. It is a collaborative effort that neatly leads stakeholders and representatives affected by the problem to design novel leadership solutions that actually work. This collection of stories, examples and narratives about exceptional leadership by design provides readers of all levels of experience with tangible, real, and heartfelt examples of how the design process can be applied to leadership. It will show how we: Inform great leadership with design; Strengthen our own leadership by design; Redesign hero leadership for more inclusivity; Redesign organizations for Fe+Male leadership synergy; Design leadership for a VUCA world; Design flow-based leadership; Design organizations that build resilient leadership; Design leadership for innovation; Design culturally intelligent leadership; Build leadership into our spaces and places
Includes index
Keywords: Business & Economics; Management: leadership & motivation; Industrial organization; Leadership; Design Thinking; Führung; Organisation; Aufsatzsammlung